A Rapid Assay of Mezlocillin Sodium by Flow-Injection Chemiluminescence Detection - Wang, Rui-Qiang; Tao, Peng-Li; Wang, Rui; Wang, Yi; Pu, Juan-Juan; Wang, Xiao-Gai; Dou, Huan-Jing; Wang, Rui-Yong (Asian Journal of Chemistry, 2013)
A new chemiluminescence method coupled with the flow injection technique for the determination of mezlocillin sodium was developed. It was based on the enhancement of mezlocillin sodium on the chemiluminescence reaction of luminol with potassium ferricyanide in alkaline medium. Under the optimum conditions, the linear range for mezlocillin sodium was from 2.0 × 10-7 to 5.0 × 10-5 g mL-1 and the limit of detection was 6.8 × 10-9 g mL-1. The relative standard deviation (n = 11) was 0.31 % for 8.0 × 10-6 g mL-1 mezlocillin sodium. The proposed method was applied successfully to the determination of mezlocillin sodium for injection with satisfactory results.